A Novel Sensitive Method to Measure Catechol-O-Methyltransferase Activity Unravels the Presence of This Activity in Extracellular Vesicles Released by Rat Hepatocytes - Casal, Enriqueta; Palomo, Laura; Cabrera, Diana; Falcon-Perez, Juan M. (Frontiers in Pharmacology, 2016)
There is a clear need for drug treatments to be selected according to the characteristics of an individual patient, in order to improve efficacy and reduce the number and severity of adverse drug reactions. One of the main enzymes to take into account in pharmacogenomics is catechol O-methyltransferase (COMT), which catalyzes the transfer of a methyl group from S-adenosylmethionine to catechols and catecholamines, like the neurotransmitters dopamine, epinephrine and norepinephrine. Although most of this enzyme is associated to intracellular vesicles, recently it has also been detected in extracellular vesicles secreted by hepatocytes and in serum circulating vesicles. COMT has implications in many neurological and psychiatric disorders like Parkinson's disease, chronic fatigue, pain response, schizophrenia and bipolar disorders. Remarkably, genetic variations of COMT affect its activity and are associated to various human disorders from psychiatric diseases to estrogen-induced cancers. Consequently, the establishment of new methods to evaluate COMT activity is an important aspect to investigate the biology of this drug-metabolizing enzyme. Herein, we have developed a sensitive and selective method to determine COMT activity. We first optimized the activity in rat liver incubated with two different substrates; norepinephrine and dopamine. The enzymatically formed products (normetanephrine and 3-methoxytyramine, respectively) were extracted by solid-phase extraction using weak cation exchange cartridges, chromatographically separated, and detected and quantified using a mass spectrometer. The range of quantitation for both products was from 0.005 to 25 μg/mL. This methodology offers acceptable recovery for both enzymatic products (≥ 75%) and good accuracy and precision (≤ 15%). The lower limit of quantifications were 0.01 and 0.005 μM for 3-methoxytyramine and normetanephrine, respectively. Importantly, this sensitive assay was able to detect the presence of COMT activity in extracellular vesicles secreted by hepatocytes supporting a potential role of these vesicles in catecholamines and catecholestrogens metabolisms. In addition, the presence of COMT activity in extracellular vesicles opens new possibilities to develop tools to evaluate personalized drug response in a low invasive manner.